Pengaruh Quick Ratio, Debt To Total Assets dan Fixed Asset Turnover terhadap Return On Asset - Siti Melani; Mia Laksmiwati (Jurnal Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the effect of Quick Ratio, Debt to Total Asset, and Fixed Asset Turnover on Return on Asset in chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research employed a quantitative approach using secondary data obtained from annual financial statements. The population consists of 12 companies, with 8 companies selected as the sample through purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, along with classical assumption tests to ensure the validity of the model. The findings show that the Quick Ratio has no significant effect on Return on Asset, while Debt to Total Asset significantly affects Return on Asset. In contrast, Fixed Asset Turnover does not significantly affect Return on Asset. These results imply that capital structure through debt plays a more dominant role in influencing profitability, whereas liquidity and fixed asset efficiency do not consistently impact financial performance. This study is expected to provide insights for company management in making financial decisions, as well as guidance for investors in assessing firm performance. In addition, the research may serve as a reference for future studies by incorporating additional financial ratios or alternative profitability indicators.